2016
DOI: 10.1051/0004-6361/201628392
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for electron-cyclotron maser emission in the solar corona

Abstract: Context. The Sun is an active source of radio emission ranging from long duration radio bursts associated with solar flares and coronal mass ejections to more complex, short duration radio bursts such as solar S bursts, radio spikes and fibre bursts. While plasma emission is thought to be the dominant emission mechanism for most radio bursts, the electron-cyclotron maser (ECM) mechanism may be responsible for more complex, short-duration bursts as well as fine structures associated with long-duration bursts. A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 23 publications
2
45
1
Order By: Relevance
“…The J-burst components observed by LOFAR (F1, F2 and H2) at frequencies below 90 MHz were imaged using LOFAR tied-array imaging described in Morosan et al (2014Morosan et al ( , 2015. The higher frequency components (>140 MHz) of the J-burst were imaged using the NRH.…”
Section: J-burst Characteristicsmentioning
confidence: 99%
“…The J-burst components observed by LOFAR (F1, F2 and H2) at frequencies below 90 MHz were imaged using LOFAR tied-array imaging described in Morosan et al (2014Morosan et al ( , 2015. The higher frequency components (>140 MHz) of the J-burst were imaged using the NRH.…”
Section: J-burst Characteristicsmentioning
confidence: 99%
“…Moreover, Zhao et al (2013) have developed a theory to explain the Type I radio burst with the ECM mechanism, which is also a long-duration continuum. In addition, Morosan et al (2016) showed that close to active regions, the ECM emission mechanism might dominate the plasma emission. This supports our conclusion.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This active region group was shown to be associated with the occurrence of solar S bursts [Morosan et al, 2016]…”
Section: Figure 3: Drift Rate As a Function Of Frequency For Solar S mentioning
confidence: 97%
“…We constructed a map of the electron densities to determine ω p (Equation (2)) and a map of the magnetic field strength to determine Ω e (Equation (3)) above this active region in order to determine if ECM emission was likely to occur instead of plasma emission [Morosan et al, 2016]. We used the method of Zucca et al [2014] to calculate the off-limb electron densities in the corona up to a height of 2.5 solar radii (R ), where 1 R is 695 Mm (see Zucca et al [2014] for further details).…”
Section: The Location Of the Active Region Noaa 11785 On The Limb (mentioning
confidence: 99%
See 1 more Smart Citation